Transformasi Lembaga Pendidikan Tinggi Islam melalui Kepemimpinan Visioner - Zainal Hakim; Yuliana Alfiyatin (Jurnal Bintang Pendidikan Indonesia, 2025)
This study explores how strategic leadership can drive institutional transformation toward excellence in Islamic higher education. A qualitative research approach with an ethnographic orientation was adopted, conducted at UIN Sulthan Thaha Saifuddin Jambi, Indonesia, for one year, specifically during the university’s preparation for national accreditation. Data were collected through three primary methods: participant observation in leadership meetings and quality assurance activities, in-depth interviews with 14 key informants (including university leaders, lecturers, and accreditation staff), and document analysis of the institution’s strategic plan and accreditation report. Data analysis employed an inductive thematic procedure, in which interview transcripts, field notes, and institutional documents were analyzed to identify emerging themes. The research findings revealed that strategic leadership is realized through three main pillars: clear visionary direction, participatory management, and the integration of Islamic humanistic values ​​into institutional governance. Despite facing challenges such as structural fragmentation, limited financial resources, and cultural resistance to change, the leadership successfully mobilized collective commitment and aligned organizational efforts with accreditation goals. As a result, the university achieved the highest national accreditation rating (A). This study contributes theoretically by contextualizing strategic leadership within faith-based educational settings in developing countries and highlighting the importance of moral authority, inclusive communication, and organizational synergy. Practically, these findings offer valuable insights for Islamic university leaders seeking to foster excellence under constraints.